Characterization of phenolic compounds in wild medicinal flowers from Portugal by HPLC-DAD-ESI/MS and evaluation of antifungal properties - Barros, Lillian (2013)
In the present work, the phenolic compounds of Castanea sativa, Filipendula ulmaria and Rosa micrantha flowers from Northeastern Portugal were characterized by HPLC-DAD-ESI/MS. Furthermore, it was performed a screening of their antifungal potential against Candida species (C. albicans, C. glabrata, C. parapsilosis and C. tropicalis). C. sativa sample gave the highest amount of phenolic compounds (18973 ± 40 µg/g, fw) and hydrolysable tannins (14873 ± 110 µg/g). The highest amounts of phenolic acids (569 ± 20 µg/g) and flavonoids (6090 ± 253 µg/g) were obtained in F. ulmaria and R. micrantha samples, respectively. Hydrolysable tannins (e.g. tri and digalloyl HHDP glucose) were the main group of phenolic compounds in C. sativa and F. ulmaria samples, while flavonoids (e.g. (+)-catechin and procyanidin dimers and trimers) were the most abundant group in R. micrantha. Thus, the stronger effect showed by this latter against all the Candida species (MIC ≤ 0.155 mg/mL) and, particularly its fungicide effects in C. glabrata, might be related to the mentioned flavonoids that were inexistence in the other samples.